2020
DOI: 10.1029/2020ja028406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Flank Magnetopause at Near‐Earth and Lunar Distances: MMS and ARTEMIS Observations

Abstract: One of the main sources of magnetospheric particles is solar wind penetration through the magnetopause-a current sheet separating the cold, dense magnetosheath from the hot, rarified magnetospheric plasmas. The mechanism responsible for magnetosheath particle transport across the magnetopause has been better investigated for the near-Earth dayside magnetopause (contrary to the nightside), where it was found that such a transport is controlled by the current sheet thickness, structure, and dynamics. Because pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 86 publications
(140 reference statements)
0
11
1
Order By: Relevance
“…In this study, we use a model where the magnetic field and plasma density across the current sheet are asymmetric while the temperature is symmetric. However, statistical studies have shown that there is typically strong temperature asymmetry in the magnetopause current sheet (Lukin et al, 2020). Using particle-in-cell simulations, Sang et al (2019) indicated that the influence of temperature asymmetry on the in-plane current (dominated by electron flow) is much weaker than that of magnetic field and density asymmetry.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we use a model where the magnetic field and plasma density across the current sheet are asymmetric while the temperature is symmetric. However, statistical studies have shown that there is typically strong temperature asymmetry in the magnetopause current sheet (Lukin et al, 2020). Using particle-in-cell simulations, Sang et al (2019) indicated that the influence of temperature asymmetry on the in-plane current (dominated by electron flow) is much weaker than that of magnetic field and density asymmetry.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this study, we use a model where the magnetic field and plasma density across the current sheet are asymmetric while the temperature is symmetric. However, statistical studies have shown that there is typically strong temperature asymmetry in the magnetopause current sheet (Lukin et al., 2020). Using particle‐in‐cell simulations, Sang et al.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A study of Artemyev et al (2017) showed that plasma and magnetic field characteristics are very similar for boundary layers observed at the lunar orbit ( ≈ 55 R E ) and farther downtail as far as ≈ 200 R E and that the dynamical magnetosheath pressure does not contribute to the pressure balance across the boundary layer at these distances. Furthermore, Lukin et al (2020) compared the characteristics of magnetic field and plasma populations during simultaneous magnetopause crossings, which are separated by about 50 R E (dayside vs night sides), and found that the magnetosheath current sheet profiles are similar at these two locations. Nevertheless, a flank magnetopause configuration and dynamics are critical for understanding the transport of magnetosheath plasma toward the magnetotail (Wing et al, 2014;Haaland et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…where B 0 = 20 nT is the magnitude of ambient magnetic field, L = 2000 km is the magnetopause scale length, and x is along the magnetopause normal (x = 0 is the center position of the magnetopause current sheet, x < 0 and x > 0 correspond to the magnetosheath and magnetosphere, respectively). We further assume the plasma number density profile based on observations (e.g., Lukin et al, 2019Lukin et al, , 2020 as follows:…”
Section: Wave-particle Interaction: Diffusion In Energy Pitch-angle S...mentioning
confidence: 99%
“…The above two examples demonstrate that the magnetic field profiles cannot be well described by the simplest Harris current sheet model, because of the significant magnetic field shear contributing to the pressure balance and making the current sheet almost force‐free. Indeed, several statistical works (Haaland et al., 2014, 2019, 2020; Lukin et al., 2019, 2020) have demonstrated that the magnetopause current sheet often has a force‐free configuration with | B | ∼ const across the sheet. Thus we use a simplified version of such force‐free current sheet model (see details and possible generalization of this model in, e.g., Allanson et al., 2015; Harrison & Neukirch, 2009b; Panov et al., 2011): B0x(x)=0,0.28emB0y(x)=B0cosh(x/L),0.28emB0z(x)=B00.17emtanh(x/L) ${B}_{0x}(x)=0,\,{B}_{0y}(x)=\frac{{B}_{0}}{\mathrm{cosh}(x/L)},\,{B}_{0z}(x)={B}_{0}\,\mathrm{tanh}(x/L)$ where B 0 = 20 nT is the magnitude of ambient magnetic field, L = 2000 km is the magnetopause scale length, and x is along the magnetopause normal ( x = 0 is the center position of the magnetopause current sheet, x < 0 and x > 0 correspond to the magnetosheath and magnetosphere, respectively).…”
Section: Wave‐particle Interaction: Diffusion In Energy Pitch‐angle S...mentioning
confidence: 99%